Comparing the effectiveness of MTK-RGO orthosis in helping spinal cord injured people to stand with the functions of other available orthoses - Mohammad Taghi Karimi; Puya Amiri; Amir Esrafilian; Mohammad Jafar Seddigh (Vesnu Publications, 2012)
Introduction: Most people with spinal cord injury (SCI) use wheelchair to move around in living areas. In order to improve their health status, however, these people do need to stand and walk with orthosis. Although lots of orthoses have been designed for paraplegic subjects, they still experience various problems using them. A new type of reciprocal gait orthosis was designed in the Bioengineering Unit of Strathclyde University to solve the problems of the available orthoses. Since there has been no research so far on the effectiveness of this new orthosis for paraplegic subjects, the present study was aimed to evaluate the new orthosis during standing of paraplegic subjects. Materials and Methods: Five paraplegic subjects whose lesion levels ranged from T4 to T12 participated in this clinical trial study. A control group including normal subjects matched with spinal cord injured individuals was also considered in this study. The stability of subjects was evaluated during quiet standing and when they were standing with either the new orthosis or the knee ankle foot orthosis (KAFO) performing hand tasks. Differences between the performances of paraplegic subjects while standing with each of these orthoses and between the functioning of normal and paraplegic subjects were compared via paired and two-sample t test respectively. Results: The stability of paraplegic subjects in standing with the new orthosis was better than that with the KAFO orthosis (P < 0.05). Moreover, the force applied on the crutch differed between the two types of orthoses. The functional performance of paraplegic subjects was better with the new orthosis and also as compared to that of normal subjects. Conclusion: The ability of the new orthosis to change the alignment of the components, the higher structural stiffness of the orthosis and better fitting was the main reasons for better operation of the new orthosis comparing to the KAFO. Keywords: Standing, Spinal cord injury, Functional hand task, Orthosis